You can't always get what you want: expectations, outcomes, and adherence of new exercisers. Issue 3 (27th May 2017) - Larson, Heather K.; McFadden, Kimberley; McHugh, Tara-Leigh F.; Berry, Tanya R.; Rodgers, Wendy M.
Abstract: Research has been unclear on how people's experiences of exercise adoption influence their outcome expectations of exercise, and how outcome expectations might relate to their continued exercise participation. The current research used qualitative description to explore the outcome expectations and perceived outcomes realised by previously sedentary adults who completed a year-long exercise programme. Participants exercised three times per week at a private university fitness facility. Semi-structured interviews were conducted with 10 women and 8 men (49.9 ± 10.2 years), several weeks after the end of the exercise programme. The interviews were audio-recorded, transcribed verbatim, and analysed using qualitative content analysis. Four primary themes emerged: (1) shifting focus from weight and appearance to living better, (2) gaining confidence through education and practice, (3) accountability/self-generated obligation to exercise for others, and (4) challenges to post-study exercise adherence. Even after completing the programme, most participants did not continue to exercise at the same frequency or intensity despite intentions to do so. The first theme suggests that it may be helpful for new exercisers to regularly reappraise their expectations and realised outcomes in order to maintain motivation for exercise. The other themes illuminate the need for exercise interventions to account for the potential difficulties of shifting from a structured programme with built-in accountability to exercising on one's own. Together, these findings provide evidence for the complex relationship between expectations, outcomes, and motivation for long-term adherence.